Exemption from the "No Work, No Pay" Principle: Paid Sick Leave and Process Wages in Indonesia - Anneke Violetta Anjani Putri; Holyness N Singadimedja; Janti Surjanti (VERITAS, 2023)
Under Law No. 13 of 2003 concerning Manpower (Labour Law), there are several rights of workers which provide the fundamental rights of workers and protect workers from unilateral termination of employment relations. In contrast, the unilateral termination of employment is an action that employers carry out to end the employment relationship process in one direction only. Thus, this action led to an industrial relations dispute resulting in â€œprocess wages,â€ which means employers should pay the workerâ€™s wages during industrial relations dispute settlement. Similarly, under Labour Law and Government Regulation Number 36 of 2021 concerning Wages (GR 36/2021), workers have the rights to be paid when absent from work due to sickness. These two conditions are the exemption of the No Work No Pay principle stated in Article 93 (1) of Labour Law and Article 40 (1) of GR 36/2021. These legal principles applied to the court decision regarding the fulfillment of workersâ€™ rights in determining their wages and compensation. Through an in-depth analysis of legal texts, court decisions, scholarly literature, and statutory framework, as well as studies based on previous cases, this research examines the application and implication of paid sick leave and process wages given to workers as an exemption from the No Work, No Pay principle. The results of this study show legal basis, compliance, and wage reckoning based on court decisions regarding the sum of paid sick leave and process wages that applied in Indonesia.